A co-operative methodology to estimate car fuel consumption by using smartphone sensors - Astarita, Vittorio; Guido, Giuseppe; Mongelli, Domenico; Giofrè, Vincenzo P. (Transport, 2015)
The European Commission has recently promoted research programs aimed at finding solutions to the ever more compelling problem of air pollution from road vehicles and has also indicated a better sustainability among the possible impacts of co-operative Intelligent Transportation Systems. In fact, many practical solutions can be developed that allow drivers and management to optimise resources and to contain costs and the emissions of pollutants by applying communication systems between vehicles (Vehicle-to-Vehicle – V2V) and between vehicles and infrastructure (Vehicle-to-Infrastructure – V2I). Along this mainstream this paper present a co-operative system which offer drivers the ability to manage their consumption and driving style, suggesting corrections to the usually adopted behaviour. The new contribution of this paper is both the co-operative approach between drivers to achieve a common goal of a better common energy consumption strategy and a methodology to estimate fuel consumption just by using Satellite data obtained from a simple smartphone. Since the fuel consumption has to be evaluated with regards to the specific vehicle type the system is based also on crowdsourcing of the specific vehicle consumption performances. The paper describes a system that gathers data on fuel consumption from the co-operating drivers that can build together the data set necessary to the system itself once they accept this paper paradigm: crowd sourced co-operation for a smarter and more sustainable transport system.